Effect of temperature increase on vegetative development, berry and wine compposition on CV. Malbec, Mendoza - Bustos Morgani, Marianela (2025)
Recent studies have predicted an increase of temperature in the main winegrowing regions of Argentina for the present century. A sustained increase in temperature may produce an advance in the phenological cycle, an increase in the concentration of berry sugar, in the alcohol content of the wines and a decrease in anthocyanins concentration, decoupling anthocyanins and sugars accumulation in the berry.